1998
DOI: 10.1046/j.1365-2486.1998.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter accumulation following fires in a moorland soil chronosequence

Abstract: Severe fires in 1957 and 1976 removed the vegetation and soil organic matter from the litter layers and organic horizons of soils at two adjacent moorland sites leaving exposed the uppermost mineral horizon of the soil. In the period since, plant recolonization and soil organic matter reaccumulation have occurred to give a chronosequence. Assuming no major changes in the carbon and nitrogen content of the unburned soil since 1957, the rates of accumulation of soil C and N were estimated to be 0.035 kg C m–2 y–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Succession of burned area after the fire, inputs from senescent leaves might have helped reaccumulation of soil organic matter but apparently it was not enough because of higher alkyl/O-alkyl-C ratios of unburned soils compared to that of burned parts in all these three sites. Haslam et al (1998) reported that forest fire that occurred previously reduced O-alkyl-C in O-horizon compared to unburned parts. In contrast, the Lapseki site which burned just before the sampling time had distinctly higher alkyl-C for the burned than unburned soils (Table 5, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Succession of burned area after the fire, inputs from senescent leaves might have helped reaccumulation of soil organic matter but apparently it was not enough because of higher alkyl/O-alkyl-C ratios of unburned soils compared to that of burned parts in all these three sites. Haslam et al (1998) reported that forest fire that occurred previously reduced O-alkyl-C in O-horizon compared to unburned parts. In contrast, the Lapseki site which burned just before the sampling time had distinctly higher alkyl-C for the burned than unburned soils (Table 5, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, carbon availability is not only an age-dependent factor, even though the effect of time and change in the quality of plant litter cannot be separated in this study (see also Ohtonen et al 1999). Haslam et al (1998) showed that the in-crease in the age and stage of decomposing OM is associated with increasing relative intensity of the alkyl-and methyl-C signal of the [ 13 C]NMR (nuclear magnetic resonance) spectra. Preston (1996) related the increasing relative intensity of these signals to the loss of easily metabolized carbohydrates and accumulation of plant biopolymers.…”
Section: Discussionmentioning
confidence: 99%
“…The general results are similar to trends noted above (Sect. 5.1) and for a moorland site (Haslam et al, 1998), mainly a relative decrease in Oalkyl C and increase in alkyl and aromatic C. While individual charred particles may be very high in aromatic C, there may actually be little change in aromatic C in bulk forest floor or surface mineral horizons of fire-affected sites. This can be the case where organic matter is consumed by fire, leaving ash rather than char, with little alteration of underlying material, or if new organic matter quickly accumulates from the pulse of detritus from fire-killed biomass and litter from regrowing vegetation.…”
Section: Qualitative Characterizationmentioning
confidence: 91%